1999
DOI: 10.1074/jbc.274.41.29453
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Rad54 Promotes Rad51-dependent Homologous DNA Pairing via ATP Hydrolysis-driven Change in DNA Double Helix Conformation

Abstract: Saccharomyces cerevisiae RAD54 gene functions in the formation of heteroduplex DNA, a key intermediate in recombination processes. Rad54 is monomeric in solution, but forms a dimer/oligomer on DNA. Rad54 dimer/oligomer alters the conformation of the DNA double helix in an ATP-dependent manner, as revealed by a change in the DNA linking number in a topoisomerase I-linked reaction. DNA conformational alteration does not occur in the presence of non-hydrolyzable ATP analogues, nor when mutant rad54 proteins defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
212
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 193 publications
(230 citation statements)
references
References 54 publications
17
212
1
Order By: Relevance
“…Stabilization of the Rad51-DNA Complex Is Independent of the ATPase Activity of Rad54 Protein-Previously, it was shown that the Rad54 K341R mutant protein, which lacks ATP hydrolysis and dsDNA unwinding activities, is still proficient in binding to both DNA and Rad51 protein (29). 2 Therefore, we tested this mutant protein with regard to its capacity to stabilize Rad51 nucleoprotein filaments.…”
Section: Rad54 Protein Stabilizes the Rad51 Nucleoprotein Filamentmentioning
confidence: 99%
See 1 more Smart Citation
“…Stabilization of the Rad51-DNA Complex Is Independent of the ATPase Activity of Rad54 Protein-Previously, it was shown that the Rad54 K341R mutant protein, which lacks ATP hydrolysis and dsDNA unwinding activities, is still proficient in binding to both DNA and Rad51 protein (29). 2 Therefore, we tested this mutant protein with regard to its capacity to stabilize Rad51 nucleoprotein filaments.…”
Section: Rad54 Protein Stabilizes the Rad51 Nucleoprotein Filamentmentioning
confidence: 99%
“…It was found that, in contrast to other proteins that stimulate the DNA pairing activity of Rad51 protein, Rad54 protein acts at a later (synaptic) stage of DNA strand exchange (24,29). Rad54 protein belongs to the Snf2/Swi2 group of proteins, which are involved in ATP-dependent remodeling of protein complexes, including mainly chromatin complexes (30).…”
mentioning
confidence: 99%
“…The Rad54 DNA supercoiling activity can be conveniently monitored by a topoisomerase-linked assay (Petukhova et al 1999;Van Komen et al 2000). Specifically, the negative supercoils generated by Rad54 are removed by Escherichia coli topoisomerase I to yield overwound (OW) DNA (Fig.…”
Section: Hed1 Ablates Functional Synergy Between Rad51 and Rad54mentioning
confidence: 99%
“…The promotion of Rad51-mediated homologous DNA pairing and strand exchange by Rad54 requires the ATPase activity of the latter and physical interaction between these two HR factors [27][28][29]. Interestingly, Rad54 dissociates Rad51 from duplex DNA via its DNA translocase activity, a function believed to be important for the intracellular recycling of Rad51 and possibly for freeing the primer end in the D-loop structure to initiate the DNA synthesis reaction [30].…”
Section: Introductionmentioning
confidence: 99%